2012
DOI: 10.1002/adma.201201912
|View full text |Cite
|
Sign up to set email alerts
|

Organic Switches for Surfaces and Devices

Abstract: The pursuit to achieve miniaturization has tantalized researchers across the fields of chemistry, physics, biology, materials science and engineering for over half a century because of its many alluring potential applications. As alternatives to traditional "top-down" manufacturing, "bottom-up" approaches, originating from the (supra)molecular level, have enabled researchers to develop switches which can be manipulated on surfaces at nanoscale dimensions with deft precision using simple external triggers. Once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
97
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(98 citation statements)
references
References 137 publications
(159 reference statements)
1
97
0
Order By: Relevance
“…In our 37 previous works, we have confirmed that no dethreading process 38 took place in formation of cucurbituril-based pseudorotaxanes due 39 to the strong binding affinity [38,39]. Moreover, an efficient 40 synthetic method for the synthesis of hetero [4]rotaxane was 41 reported by Wu using a new ''threading-stoppering-followed by-42 clipping'' approach [40]. Based on the above consideration, herein, 43 we designed and synthesized a novel ammonium backbone, which 44 contained three ammonium units.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…In our 37 previous works, we have confirmed that no dethreading process 38 took place in formation of cucurbituril-based pseudorotaxanes due 39 to the strong binding affinity [38,39]. Moreover, an efficient 40 synthetic method for the synthesis of hetero [4]rotaxane was 41 reported by Wu using a new ''threading-stoppering-followed by-42 clipping'' approach [40]. Based on the above consideration, herein, 43 we designed and synthesized a novel ammonium backbone, which 44 contained three ammonium units.…”
supporting
confidence: 81%
“…As a type of classic topological structure, the 12 mechanically interlocked molecules such as rotaxanes and 13 catenanes have unique structural features and can be applied in 14 various fields, including molecular devices, molecular switches 15 and machines, nanotechnology, biological technology, drug deliv- 16 ery and polymer materials [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. 17 Accordingly, the design and construction of mechanically 18 interlocked molecules with multiple topology units has become 19 one of the most important projects.…”
mentioning
confidence: 99%
“…The entire fields of supramolecular and mechanically interlocked molecular switches [26,69,70] are a testament to the fact that there are numerous examples of how to reversibly dissociate templates from their reacted substrates. In the context of the mechanical bond, however, this reversible dissociation becomes relative intramolecular motion, and has often been exploited to harness the energy from these well-defined nanoscale movements, leading to applications such as molecular muscles [71], actuators [71], memory [72], unidirectional motion [73][74][75] and sequence-specific peptide synthesis [76].…”
Section: Dissociation Of the Reacted Substrates With The Templatementioning
confidence: 99%
“…The possibility to develop artificial molecular machines as a new sort of complex materials with multiple components hierarchically assembled to perform programmed functions has become an area of great interest [1][2][3][4]. In this field, amphidynamic crystals based on molecular rotors are capable of emulating the structure and function of macroscopic devices [5][6][7][8][9] such as gyroscopes and compasses.…”
Section: Introductionmentioning
confidence: 99%